2019
DOI: 10.1186/s12889-019-7430-9
|View full text |Cite
|
Sign up to set email alerts
|

Work-related risk factors and the prevalence of low back pain among low wage workers: results from a cross-sectional study

Abstract: Background Low back pain, the most commonly reported musculoskeletal problem, is a major burden on individuals, health systems and social care systems with the indirect cost being predominant. It results in disability, poor service, low quality of life and sickness absences in working places. The problem of low back pain and its risk factors among hotel housekeepers are not well known in Ethiopia. Therefore, this study was aimed to investigate the prevalence and identify determinants of low back p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 28 publications
4
46
1
8
Order By: Relevance
“…This specific ambiguity of the results of the present study can be reflected in the results of previous research. Some of them show that the severity and the levels of LBP where higher in the groups of participants with fewer years of work (Lallukka et al, 2018;Wami et al, 2019), while others surveys present their results that more years of work contribute to higher levels and more severe incidents of LBP (Loy et al, 2010). The conclusion that follows from the above is that the results of the present research are ambiguous, just like the results of previous research and no clear picture can be deduced.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This specific ambiguity of the results of the present study can be reflected in the results of previous research. Some of them show that the severity and the levels of LBP where higher in the groups of participants with fewer years of work (Lallukka et al, 2018;Wami et al, 2019), while others surveys present their results that more years of work contribute to higher levels and more severe incidents of LBP (Loy et al, 2010). The conclusion that follows from the above is that the results of the present research are ambiguous, just like the results of previous research and no clear picture can be deduced.…”
Section: Discussioncontrasting
confidence: 60%
“…More specifically, the results of studying the relationship between LBP and with limited activity show a positive association of the intensity of LBP and age, and years of work (Loy, Warner-Czyz, Tong, Tobey, & Roland, 2010). On the contrary, a different survey (Wami, Abere, Dessie, & Getachew, 2019) regarding LBP among hotel employees showed that these employees with fewer working years had higher rates of LBP compared to those who had many years of work. In 2018 Lallukka and associates, after 28 years of research in the field, concluded that employees with few years of work presented statistically significantly higher levels of LBP compared to those who already worked for more years.…”
Section: Introductionmentioning
confidence: 99%
“…In other recent studies also undertaken in Saudi Arabia among specific professional groups, the point prevalence of LBP found was 80% in nurses [ 10 ], 57.3% in male high school teachers [ 13 ], 55% among faculty members [ 29 ], 40.5% in medical students [ 30 ], 51.6% in taxi drivers, 31.4% in office workers [ 31 ], and 21.2% among health sciences students [ 32 ]. Hence, in most of these cases, the point prevalence was higher than in our study, which could be related to the burden of work, type of professional or academic activity carried out by each group, and poor posture at work [ 33 ]. Worldwide, the LBP´s point prevalence found in countries such as Canada, the United States, Sweden, Belgium, Finland, Israel, and the Netherlands ranges between 1.4 and 20.0% [ 3 ].…”
Section: Discussionmentioning
confidence: 86%
“…However, chronic pain is associated with high productivity losses due to sick leave and unemployment, partly due to comorbidity with mood disorders [39], which increases the vulnerability of people suffering from pain [40]. Low-wage workers and those with worse working conditions are at higher risk of developing pain-related disorders and experience barriers to accessing quality care, which could hinder recovery [41,42].…”
Section: Discussionmentioning
confidence: 99%